The Formulation Policy on Corporate Criminal Liability System For The 1950 - 2017 Period and Its Harmonization in The Renewal of National Criminal Law - Dwidja Priyatno; Kristian Kristian (Universitas Kuningan, 2018)
The Criminal Code (KUHP) which currently applies does not recognize corporations as the subject of criminal acts. Therefore, the formulation/legislation policy concerning corporate criminal liability system in Indonesia is only regulated in various specific criminal laws (lex specialis). This research discusses the formulation/legislation policy regarding the corporate criminal liability system in 124 special criminal legislations outside the Criminal Code (KUHP) from 1950-2017. This research used a normative juridical research method as well as interpretation method with a policy-oriented approach. Types and sources of data used were secondary data in the form of primary, secondary, and tertiary legal materials. The collected data were then analyzed based on qualitative analysis method. The results of the research showed that the corporate criminal liability system in legal politics in Indonesia (especially in the formulation/legislation policy) still experiences disorientation and disharmonious. Besides, the national law development should follow every development and/or change of society that is developing in the direction of modernization and globalization and should be able to accommodate all society’s needs in various fields. This legal development should be continuously carried out (as a dynamic and an endless process) by